2010
DOI: 10.1177/1753193409352713
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanism of Injury for Scaphoid Fractures: ‘Test Your Strength’ Punch-Bag Machines

Abstract: We investigated the mechanism of injury in a consecutive series of 153 confirmed scaphoid fractures. We found that ten (6%) occurred as a result of using a 'test your strength' punch-bag machine, a device found in public houses and amusement arcades. Clinicians should be aware that scaphoid fractures can occur as a result of punching these machines or other similar objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The increasing number of punching-or assault-related injuries are becoming more prominent in the literature. 15,16 Our data are comparable to other literature with the mean age of true scaphoid fractures ranging from 25 years to 35 years and a type B unimodal young male distribution. 2,3,17,18 A male predominance was observed, but not as great as some studies have suggested.…”
Section: Discussionsupporting
confidence: 93%
“…The increasing number of punching-or assault-related injuries are becoming more prominent in the literature. 15,16 Our data are comparable to other literature with the mean age of true scaphoid fractures ranging from 25 years to 35 years and a type B unimodal young male distribution. 2,3,17,18 A male predominance was observed, but not as great as some studies have suggested.…”
Section: Discussionsupporting
confidence: 93%
“…A previous report indicated that scaphoid and trapezoid fractures accounted for 68.2% and 0.4% of all carpal bone fractures, respectively [4]. With respect to the mechanism of injury, there are some reports on scaphoid fractures due to punching [5, 6]. However, the simultaneous occurrence of trapezoid and scaphoid fractures in sports has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Football, basketball, cycling, and skateboarding have all been associated with an increased risk of fracture, although this varies depending on study origin 15,16 . Scaphoid fractures also result from recreational punching or assault 18,19 . Two studies have reported that male sex and sports injuries are risk factors that are associated with true fractures 8,20 .…”
Section: Epidemiologymentioning
confidence: 99%